DIDAKTISME DALAM CERPEN PELANGI IBU KARYA AFIFAH AFRA - A'yun, Insiya Qurotul; Turahmat, Turahmat (Universitas Negeri Surabaya, 2019)
Short story of Pelangi Ibu by Afifah Afra works as an object in writing this article. The short story by Afifah Afra tells the story of a mother who has lost the love of her children because her children are studying or working away from her home. The approach used alone is a didactic approach. This research itself is a type of qualitative research. This research was conducted by beginning to read the short story before conducting research. The research was conducted by looking for didactic elements from the short story.Short story of Pelangi Ibu by Afifah Afra works as an object in writing this article. The short story by Afifah Afra tells the story of a mother who has lost the love of her children because her children are studying or working away from her home. This research used qualitative approach. The approach used alone is a didactic approach. This research itself is a type of qualitative research. This research was conducted by beginning to read the short story before conducting research. The research was conducted by looking for didactic elements from the short story.